2014
DOI: 10.1002/brb3.247
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of fatigue in Japanese patients with Parkinson's disease

Abstract: BackgroundFatigue is a common nonmotor symptom of Parkinson's disease (PD). Although the causes of fatigue were estimated in the previous reports, fatigue is not fully understood. To determine the frequency of and factors related to fatigue in patients with PD, we carried out clinical assessments in our university hospital.MethodsWe used the Japanese version of the Parkinson Fatigue Scale (J-PFS). The J-PFS was administered to 110 patients with PD, and a cutoff point of 3.3 was used for the diagnosis of fatigu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 37 publications
(56 reference statements)
1
22
0
Order By: Relevance
“…The relation between fatigue and age was reported in 24 studies, two of which found an association between fatigue and higher age. The meta‐analysis for age showed that patients with fatigue were, on average, 1.4 years older than those without fatigue (for the forest plot, see Supplementary Material 5).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…The relation between fatigue and age was reported in 24 studies, two of which found an association between fatigue and higher age. The meta‐analysis for age showed that patients with fatigue were, on average, 1.4 years older than those without fatigue (for the forest plot, see Supplementary Material 5).…”
Section: Resultsmentioning
confidence: 92%
“…Demographic features, disease severity, cognitive impairment, and depression did not exert significant effects on prevalence estimates. Following Barone and colleagues, we contrasted studies on de novo (five of 44 studies) versus studies on treated PD patients in which the same scale was used (28 studies). This contrast did not show differences in fatigue prevalence between treated and de novo PD patients (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Other studies in literature have suggested a prevalence rate from 33% to 58%. This variation can be contributed to heterogeneity in the methods of diagnosis, scales used and definition of “fatigue.”[131415]…”
Section: Discussionmentioning
confidence: 99%
“…This observation is in line with Japanese and Brazilian studies which also showed a positive correlation between the duration of disease and fatigue, suggesting fatigue to be intrinsic to the PD itself. [141617] Thus, as the duration of disease increases, the nonmotor complications such as fatigue, a key NMS in PD patients also increases proportionately.…”
Section: Discussionmentioning
confidence: 99%
“…Fatigue is a prevalent disabling non-motor symptom in PD (11). The mechanisms of fatigue are ill understood, but it has been associated with gait problems (12) and may have an impact on rehabilitation (13). Attentional strategies by means of verbal instructions were proposed as an alternative method for cues and were shown to have similar short-term effects (1416).…”
Section: Introductionmentioning
confidence: 99%